Penerapan Model UTAUT terkait akseptasi mahasiswa terhadap Cashless Payment di masa Pandemi COVID-19 - Rizka Elisa Rahmawati; M Ruslianor Maika (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
This study aims to determine the level of student acceptance of the cashless society era which is now being promoted by the Government as an effort to stop the spread of the Covid-19 virus in Indonesia. The occurrence of coronavirus transmission through physical contact or droplets makes people have to keep their distance and reduce the intensity of social interaction with other people. Therefore, public awareness is needed to reduce the use of cash transactions which are one of the means of spreading Covid-19 and switch to non-cash payments so that they can continue to carry out economic activities, which are the spearheads of human life. The method chosen by the author was qualitative as a combined research method with a phenomenological approach that was carried out directly to students about the changes that occurred during the pandemic. The results showed that the level of student acceptance of cashless payments was quite good with 85% of respondents using non-cash payments and this will continue to grow along with the provision of more modern technology and according to student interests.